Qatar Foundation Annual Research Conference Proceedings Volume 2016 Issue 1 2016
DOI: 10.5339/qfarc.2016.eepp2131
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Partial Electrocoalescence by Level-Set and Finite Element Methods

Abstract: The coalescence of a water drop in a dieletric oil phase at a water layer interface in the presence of an electric field is simulated by solving the Navier-Stokes and charge conservation equations with the finite element method. The proprietary software Comsol Multiphysics is used for this purpose. The interface between the oil and water phases is tracked by implementing a Level Set approach. The sensitivity of the model with respect to some input parameters are reported. In particular, the calculations are se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 19 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…The Level-Set method is employed to track the boundaries between continuous oil phase and dispersed water phase. The location of interface is obtained by solving the transport equation of the Level-Set function , described by =0.5 [23,32]. The evolution of the boundary is given by Eq.…”
Section: Model Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Level-Set method is employed to track the boundaries between continuous oil phase and dispersed water phase. The location of interface is obtained by solving the transport equation of the Level-Set function , described by =0.5 [23,32]. The evolution of the boundary is given by Eq.…”
Section: Model Descriptionmentioning
confidence: 99%
“…We follow the approach of Vivacqua et al [32], coupling Eq. (1) with the Navier Stokes equations for the flow and Laplace equations for the electric field.…”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…decreases to 0 exponentially outside and inside the droplet, respectively. We follow the approach of Li et al [20] and Vivacqua et al [36], coupling Eq. 3with the Navier Stokes equations for the flow and Laplace equations for the electric field.…”
Section: Model Descriptionmentioning
confidence: 99%
“…The water phase in crude oil contains dissolved salts, which influence water conductivity significantly. Vivacqua et al [36] developed a Level-Set approach to model the electrocoalescence and found numerically that as the conductivity was increased, partial coalescence produced larger secondary droplets and the largest was at 10 -3 S m -1 . Moreover, Hamlin et al [37] reported the existence of a critical conductivity, below which the droplets partially coalesced, while above which the droplets bounced off each another.…”
Section: Introductionmentioning
confidence: 99%